The protective effects of wellbeing and flourishing on long-term mental health risk - Richard Andrew Burns; Timothy Windsor; Peter Butterworth; Kaarin Jane Anstey (Elsevier, 2022)
Objective: Personal wellbeing reflects individuals' experiences of positive mental health and those with high wellbeing can be described as flourishing. Increasingly, wellbeing and flourishing are informing public health policy and clinical practice. However, the long-term benefit of wellbeing and flourishing on negative mental health outcomes over the life course is not widely explored. Method: Data were from the Personality and Total Health Through Life study, based in Canberra, Australia. Participants were recruited to three age cohorts (Early Adulthood n ​= ​991; Middle Adulthood n ​= ​1,510; Later Adulthood n ​= ​1,432). Wellbeing was operationalised by positive and negative affect, life satisfaction, morale, resilience and social support. Flourishing status was defined by those reporting the highest levels of wellbeing. Mental Health was operationalised by depression and anxiety symptoms, and any depressive disorder. A sub-set of early (n ​= ​439) and middle adulthood (n ​= ​1,275) participants completed the Composite International Diagnostic Interview (CIDI). Results: Associations between individual wellbeing indicators with mental health were mostly attenuated or of small magnitude in multivariate analyses, except for negative affect and low mastery which consistently reported substantial 4-year risk for all age cohorts. In contrast flourishing status reported consistently strong protection against poor mental health outcomes. Conclusion: Individual wellbeing indicators are not as strongly related to mental health outcomes as a higher-order latent wellbeing factor reflecting flourishing. However, multiple measures of wellbeing are needed to capture the gamut of wellbeing experiences and are related to improved mental health outcomes over the long-term and are generally consistent across adulthood.